2017
DOI: 10.15419/jmri.86
|View full text |Cite
|
Sign up to set email alerts
|

ACE Alzheimer’s: The Role of Vitamin A, C and E (ACE) in Oxidative Stress induced Alzheimer’s Disease

Abstract: Alzheimer's disease (AD), a chronic neurodegenerative disease which is known to progress gradually and has now become a substantial health concern through-out the world. Clinically, cognitive declination and progressive dementia are the main characteristics of AD while pathologically; Aß plaques and tau-neurofibrils are the hallmarks. The present literature search has suggested that oxidative stress is one of the most vital risk factor which can potentially lead to the development of AD. Oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…(2) elimination of LPO products [108,109]. Prevention of LPO products formation is a primary successful method with anti-oxidants such as vitamin C and vitamin E are inhibits the LPO [110]. The alternative method of LPO inhibition is deuteration of PUFA at double bond of methylene bridges (bis-allylic sites) leads to reduce the chain reaction process [111].…”
Section: Inhibiting Of Lpo Productsmentioning
confidence: 99%
“…(2) elimination of LPO products [108,109]. Prevention of LPO products formation is a primary successful method with anti-oxidants such as vitamin C and vitamin E are inhibits the LPO [110]. The alternative method of LPO inhibition is deuteration of PUFA at double bond of methylene bridges (bis-allylic sites) leads to reduce the chain reaction process [111].…”
Section: Inhibiting Of Lpo Productsmentioning
confidence: 99%
“…OS can also lead to alterations in the structure of proteins, and impaired protein structures can further exacerbate oxidative damage [9]. Indeed, ROS causes protein oxidization and modi ied protein structures that easily aggregate and dimerize [30]. These functionally and structurally abnormal oxidized proteins then accumulate within the cytoplasm of neurons in the form of Aß plaques and tau neural ibrillary tangles (NFT) [31].…”
Section: Oxidative Damagementioning
confidence: 99%
“…These functionally and structurally abnormal oxidized proteins then accumulate within the cytoplasm of neurons in the form of Aß plaques and tau neural ibrillary tangles (NFT) [31]. Aß plaques themselves are also known to be responsible for the formation of ROS, resulting in a continuous cycle of OS [30]. In addition, a growing body of evidence has demonstrated that ROS causes oxidative damage to lipids and DNA, which leads to various cellular dysfunctions [4,32,33].…”
Section: Oxidative Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, vitamin A and C and E have been shown to reduce the risk of many diseases including Alzheimer's diseases [11]. Dietary polyunsaturated fatty acids have also known to have immunomodulatory and other beneficial health-promoting effects [12].…”
mentioning
confidence: 99%